Komodifikasi Keluarga dalam Dunia Virtual untuk Peningkatan Ekonomi di Era Revolusi Industri 4.0 - Khairul Syafuddin (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2020)
The development of industry 4.0 begins with the emergence of internet technology that can connect the entire community without the constraints of space and time. Industry 4.0 also gave rise to a society 5.0 oriented to all problems that could be solved through technology. One problem in society is the economic problem. In families living in the industrial era 4.0, these problems can be faced through internet technology. One way is to make daily life in the family into a spectacle. To realize this, then family life needs to be used as a commodity so that it can carry out the process of commodification. The process of commodification of spectacle in this virtual world can be done through platforms offered via the internet, one of which is Youtube. One example of a Youtube account that successfully commodifies family life in the industrial era 4.0 is Li Ziqi's account. His creativity in creating content and making family life narratives can be one example of references for families to make use of the internet in generating profits. Through Youtube, families can also commercialize the content they make as a sign that the commodification process is successful.